Warisan Sikap Rahmah El Yunusiyyah Dalam Mendidik Perempuan - Sartika, Diana; Iswantir, Iswantir; Hayati, Syarifatul; Suharto, Sulasmi (Institut Agama Islam Sumatera Barat Pariaman, 2024)
Rahmah El Yunusiyyah views that every woman must be educated, because according to her, in the hands of educated women, a quality generation will be born. For this reason, Rahmah El Yunusiyyah established a special school for women called Perguruan Diniyyah Puteri. This study aims to discuss how Rahmah El Yunusiyyah built the Diniyyah Puteri College and from Rahmah El Yunusiyyah's struggle what characteristics we can emulate as a woman in particular. This research uses the Libarary Research method which uses various literature. There are 18 pieces of literature about Rahmah El Yunusiyyah in this research. To discuss about Rahmah El Yunusiyyah. From the discussion of the research results, it is found that Rahmah El Yunusiyyah founded a school because when she attended her eldest brother Zainuddin Labay's school she felt that not all educational problems could be discussed in the class because of the joining of men and women in one class. For this reason, Rahmah El Yunusiyyah founded the Diniyyah Puteri College on November 1, 1923 when she was 23 years old. In building Diniyyah Puteri, she faced many challenges. But she overcame these challenges with her traits such as commitment to education, ability to deal with failure and optimism in achieving predetermined goals.